Remote sensing at the Centre for Geophysical Research, University of Costa Rica - Amador Astúa, Jorge Alberto (1993)
The background of the remote sensing technology in the Central American region is discussed. A brief account is given of the present state of remote sensing in Costa Rica. Although the remote sensing technology was introduced in Costa Rica and in the Central American region in the mid 1970s, it has not had a widespread use yet, specially due to economical contraints and the lack of technical and training facilities. In this respect, special attention has been given to the role of the University of Costa Rica in the transfer and application of this technology. Also, some conclusions are stated pertaining the future of remote sensing in the country.